Television journalism - Cushion, Stephen (London ; Thousand Oaks, Calif. : SAGE, 2012)
"Covering issues of ownership, control, policy, and regulation, the book is a blend of theory and history that examines the UK industry from a comparative perspective. It establishes the importance of television journalism, how it converges with other formats, and the ways in which it can survive an ever-changing terrain with the advent of new technologies and new media."--Publisher.
The role of news in television culture: current debates and practices in contemporary journalism -- From radio to television: making sense of broadcasting history -- Redefining what's newsworthy: towards 24-hour news values and conventions? -- The rise of partisan news consumption: towards a polarisation of television journalism and audiences? -- Reporting the politics of devolved nations: towards more localised television news? -- Entering the profession: who are television journalists? -- Putting television news centre stage: the past, present and future shape of journalism scholarship.
Includes bibliographical references and index.
Keywords: Television broadcasting of news